Advances in autonomous robotics systems : 15th Annual Conference, TAROS 2014, Birmingham, UK, September 1-3, 2014. Proceedings - Leonardis, Ales; Witkowski, Mark; Melhuish, Chris; Mistry, Michael (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 15th Conference on Advances in Autonomous Robotics, TAROS 2014, held in Birmingham, UK, in September 2014. The 23 revised full papers presented together with 9 extended abstracts were carefully reviewed and selected from 48 submissions. The overall program covers various aspects of robotics, including navigation, planning, sensing and perception, flying and swarm robots, ethics, humanoid robotics, human-robot interaction, and social robotics.